Pelatihan Pembuatan Mading Dua Dimensi di SMPN 30 Surabaya - Windi Setiawan; Imayah Imayah; Edy Widayat (IKIP PGRI Bojonegoro, 2020)
ABSTRACT The wall magazine is one of the means to gather students' creativity at school. Its existence indirectly is able to make students to dare to express their creative ideas in the form of poetry, short stories, or other works that can be visualized. SMPN 30 Surabaya is a school that has complete facilities. It's just that bulletin boards at the school don't attract students to work. So, there is a need for training in making two-dimensional wall magazine to make it more interesting. The Unitomo Community Service Team is conducting training in this regard. The assistance was carried out in three stages namely. The planning phase, the implementation phase, and the reflection phase. At the planning stage, the service team and partners coordinate about the time of service delivery. At the implementation stage, the service team provides assistance to students in making two-dimensional wall stickers. Then, at the reflection stage, the service team and partners discussed the sustainability of bulletin boards so that they could run in a sustainable manner. Keywords: magazine, wall magazine, two dimensions ABSTRAKMajalah dinding adalah salah satu sarana untuk menghimpun kreatifitas siswa-siswi di sekolah. Keberadaanya secara tidak langsung mampu membuat siswa untuk berani mengeluarkan ide kreatifnya baik dalam bentuk puisi, cerita pendek, atau karya lain yang dapat divisualisasikan. SMPN 30 Surabaya adalah satu sekolah yang memiliki fasilitas lengkap. Hanya saja papan buleting di seolah tidak menarik siswa untuk berkarya. Sehingga mereka membutuhkan pelatihan pembuatan mading dua dimensi agar tampak lebih menarik. Tim pengabdian masyarakat Unitomo kali ini melakukan pelatihan berkaitan dengan hal tersebut. Pendampigan dilaksanakan dalam tiga tahap yaitu tahap perencanaan, pelaksanaan, dan refleksi. Pada tahap perencanaan, tim pengabdi bersama mitra berkoordinasi mengenai waktu pelaksanaan pemgabdian. Pada tahap pelaksanaan, tim pengabdi melakukan pendampingan kepada siswa dalam membuat mading dua dimensi. Selanjutnya, pada tahap refleksi, tim pengabdian dan mitra mendiskusikan mengenai keberlanjutan mading agar bisa berjalan secara berkesinambungan. Kata Kunci: majalah, majalah dinding, dua dimensi